Quiet Signals of Burmeister's Porpoises ( Phocoena spinipinnis ) Recorded in Chile and Peru - Ruth Ortés‐Villauriz; Magnus Wahlberg; Daniel A. Gómez‐Lobo; Joanna Alfaro‐Shigueto; Sonja Heinrich; Jeffrey C. Mangel; Clara Ortiz‐Alvarez; Morgan J. Martin (Marine Mammal Science, 2026)
Burmeister's porpoises are cryptic and challenging to detect visually. More information on their acoustic signals could facilitate the use of passive acoustic monitoring (PAM) and help to better understand their ecology. Here, clicks were recorded from two different Burmeister's porpoise populations, one in Chile and the other in Peru, using a 4‐channel hydrophone array and a single‐channel hydrophone recorder. Burmeister's porpoises produced narrowband high‐frequency (NBHF) echolocation clicks, typical of all species of porpoises and a few other odontocete species. Feeding buzzes and burst‐pulse sounds, likely used for communication, were also recorded. Echolocation click frequency parameters resembled those of harbor porpoises, with a peak frequency of 137 ± 2 kHz and a rms bandwidth of 7 ± 3 kHz, but duration was longer (132 ± 39 μs) than clicks from other NBHF odontocetes. Echolocation click source levels (137 ± 13 dB re 1 μPa rms) and energy levels (100 ± 13 dB re 1 μPa 2 s at 1 m) were considerably lower than clicks from other NBHF species. The quiet signals used by Burmeister's porpoises affect maximum detection range of prey as well as conspecific communication. Low source levels may prevent porpoises from being detected by predators and aid echolocation in cluttered environments. When designing PAM efforts for this species, low source levels should be considered as the longer durations only partly compensate for the detectability of these signals.